Gut microbiota modulation in the chronic kidney disease management - Łukasz Dobrek (Farmacja Polska, 2022)
Chronic kidney disease (CKD) is a systemic disease that develops as a consequence of progressive and irreversible damage to the structure of the kidneys, which leads to impairment of the homeostatic excretory, metabolic and regulatory functions of the kidneys. The final consequence is end-stage renal failure which requires renal replacement therapy. The main etiological factors of CKD are: diabetes, arterial hypertension, glomerulonephritis, tubulointerstitial nephritis, and polycystic kidney disease. Less common causes include: obstructive nephropathy, connective tissue diseases, sarcoidosis, or amyloidosis. The pathogenesis of CKD is related to the progressive loss of nephrons, with hyperfiltration and pressure overloading of the remaining ones, which accelerates their decompensation. As a consequence, a systemic retention of uremic toxins and retention of sodium and water develop. Low-grade inflammation and increased oxidative stress resulting from disturbed interaction between dysfunctional kidneys and the gastrointestinal microbiota (“kidney-gut axis”) also play an important role in CKD pathogenesis. The reduction of glomerular filtration rate, retention of uremic toxins, disturbances in acid-base regulation cause quantitative and qualitative changes in the composition of the gut microbiota, leading to a state of dysbiosis and an increase in the permeability of the intestinal barrier. This condition leads back to bacteremia and an increase bacteria-derived toxins in the blood, that maintain the systemic low-grade inflammation and oxidative stress that exacerbate kidney damage. The impaired kidney-gut axis in the course of CKD may be modified by the use of preparations affecting the composition of the intestinal microbiota and restoring the eubiosis state - prebiotics, probiotics and synbiotics. The paper briefly discusses the experimental and clinical studies evaluating the influence of the abovementioned preparations on the course of CKD. The encouraging preliminary results suggest that the supplementation with these preparations may be an important therapeutic option for CKD management in the future. However, the further, large clinical trials are needed to confirm the preliminary conclusions in this regard.